2018
DOI: 10.6090/jarq.52.339
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Bluish Flower Color of Transgenic Chrysanthemum by Interspecific Hybrids

Abstract: Bluish transgenic chrysanthemums have already been produced and are expected to be commercialized. As domesticated chrysanthemum (Chrysanthemum morifolium) is known to cross with wild species native to Japan, the risk of transgene flows into the wild population must be considered. However, little research has been conducted on the crossability of transgenic chrysanthemums or on the heritability of the transgenes involved. In this study, we investigated artificial cross-pollination between color-modified chrysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…japonense. The use of 'Sei Arabella' or T37 as the pollen parents showed higher seed set rates (from 70.7% to 83.4%) than those obtained with 'Taihei' (from 28.8% to 43.1%, Aida et al 2018). These results demonstrated that cultivated chrysanthemums, including the color-modified transgenic plants, readily cross with C. japonense var.…”
Section: Cross Fertilization Between Chrysanthemums Andmentioning
confidence: 78%
See 2 more Smart Citations
“…japonense. The use of 'Sei Arabella' or T37 as the pollen parents showed higher seed set rates (from 70.7% to 83.4%) than those obtained with 'Taihei' (from 28.8% to 43.1%, Aida et al 2018). These results demonstrated that cultivated chrysanthemums, including the color-modified transgenic plants, readily cross with C. japonense var.…”
Section: Cross Fertilization Between Chrysanthemums Andmentioning
confidence: 78%
“…For crossing experiments, the ray florets were removed before flowering with the heads being bagged. Given the generally low self-pollination rate of chrysanthemum (Wang et al 2014, Aida et al 2018, pollinations were performed without emasculation. To monitor selfpollination, three bagged heads within each crossing combination were not artificially pollinated.…”
Section: Crossing and Seed Germination Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, inter-specific crossability of transgenic blue chrysanthemum developed by Noda et al [ 40 ] with the wild species Chrysanthemum japonense var. japonense was checked [ 121 ]. This study demonstrated the heritability of the transgene and confirmed the transmission of the transgene to interspecific progeny.…”
Section: Breeding For Anthocyaninsmentioning
confidence: 99%
“…Furthermore, the progeny also accumulated anthocyanins that were specific to the parent plant. This provides basic information that may be used to prevent transgene flow to native chrysanthemum species in order to commercialize the blue-hued varieties [ 121 ]. Intriguingly, our work on the breeding of new chrysanthemum cultivars for novel floral colors using inter- and intra-specific breeding has resulted in a large number of cultivars exhibiting alluring flower hues.…”
Section: Breeding For Anthocyaninsmentioning
confidence: 99%